Strategi BP3MI Dalam Mengatasi Masalah Pekerja Migran Indonesia Ilegal Di Provinsi NTT - Kaha, Hendrikus Likusina; Lawalu, Stephanie Perdana Ayu; Matta, Rian Petrus Pati; Lawalu, Stephanie (Department of Public Administration, Muhammadiyah University of Makassar, 2025)
Illegal migrant workers remain a major challenge, especially in areas with high migration rates such as East Nusa Tenggara (NTT). The Indonesian Migrant Workers Protection Service Center (BP3MI) of NTT Province, as the spearhead of PMI protection in the region, faces multidimensional challenges in addressing this issue. Some of those challenges are limited resources, a lack of public awareness, and weak law enforcement against syndicates that facilitate illegal migration. This research uses a qualitative approach, with data gathered by interviews, observation, and documentation. Based on the strategy theory by Fred R. David, there are three stages in obtaining BP3MI-NTT’s goal in reducing the number of illegal migrant worker issues, such as policy formulation, policy implementation, and policy evaluation. Results show that besides three stages of policy strategies, BP3MI has performed unique strategies in influencing people to become legal migrant workers, such as using church pulpit messages, as well as building collaboration with various parties. Despite three stages of policy strategies that have been implemented by BP3MI-NTT, this research also finds that up until the end of 2025, the number of illegal migrant worker issues is still high (588 cases). Even though BP3MI of NTT Province is still not reaching its overall goals, these three strategies show that the institution is moving forward to reduce the number of illegal migrant worker issues in NTT.